Implementasi Pendewasaan Perkawinan Terhadap Dispensasi Kawin Dalam Perspektif Hukum Positif Di Indonesia - Dinny Wirawan Pratiwie; Karina Lizwary (Yuriska: Jurnal Ilmiah Hukum, 2023)
Background: According to Article 7 paragraph (1) of Law Number 1 of 1974, marriage is permitted if the man has reached the age of 19 and the woman has reached the age of 16. These provisions have been amended, namely in Article 7 paragraph (1) of Law Number 16 of 2019, it is explained that marriage is only permitted if a man and a woman have reached the age of 19. Marriage maturity is a program of the Family Planning Population Agency (BKKBN) as an effort to increase the minimum age of 20 years for women and 25 years for men to have their first marriage. Marriage dispensation is a legal policy that allows minors to be able to enter into legal marriages in Indonesia as stipulated in Article 7 paragraph (2) of the Marriage Law. Research Method: In this study the authors used normative research methods with conceptual approaches to laws, cases. Findings: Marriage Age Maturity (PUP) is an effort to increase the age of the first marriage, so that it reaches a minimum age at the time of marriage, namely 21 years for women and 25 years for men. Maturity of marriage age is not just delaying until a certain age, but trying to make the first pregnancy occur at a fairly mature age. With permission from the court or related officials for someone who is not yet 19 years old and wants to get married for certain reasons and accompanied by supporting evidence. So that the provisions for the legal age limit for marriage can be dissolved with the dispensation of marriage, it does not rule out the possibility that child marriages will continue to occur. Conclusion: The application of the marriage dispensation is in stark contrast to efforts to prevent child marriage in the marriage-age maturity program and contradicts Article 26 paragraph 1 letter c, the 2002 Child Protection Law which mandates preventing marriage at a young age. This provision opens a legal loophole for the implementation of child marriages.